The Effect of Epidural Steroid Injection on Postoperative Outcome in Patients From the Lumbar Spinal Stenosis Outcome Study. Issue 16 (15th August 2015) - Fekete, Tamas; Woernle, Christoph; Mannion, Anne F.; Held, Ulrike; Min, Kan; Kleinstück, Frank; Ulrich, Nils; Haschtmann, Daniel; Becker, Hans-Juergen; Porchet, Francois; Theiler, Robert; Steurer, J.
<x xml:space="preserve">Abstract</x> Study Design. Retrospective analysis of data from patients participating in the Lumbar Spinal Stenosis Outcome Study (LSOS). Objective. The aim of LSOS was to assess clinical outcomes after surgical or nonoperative treatment in patients with and without prior epidural steroid injections. Summary of Background Data. Epidural steroid injections (ESI), a common treatment modality, reduce symptoms in the short-term, but according to a subgroup analysis from the Spine Patient Outcomes Research Trial (SPORT) they reduce the amount of improvement after subsequent surgical or nonoperative treatment. Methods. The data of 281 patients with lumbar spinal stenosis who had completed baseline and 6-month follow-up assessments were analyzed. Patients completed the Spinal Stenosis Measure (SSM). Changes in the SSM scores from baseline to follow-up were compared between patients with and without prior ESI, for the surgical and nonsurgical treatment groups. Results. The mean (SD) age of the patients was 75 (8.7) years. 229 patients underwent surgery and 111 of these had received an ESI in the 12 months before surgery. Of the 52 patients treated nonoperatively, 29 had received a prior ESI. The unadjusted changes (improvement) in the SSM-symptom scores between baseline and 6 months' follow up were: surgery and prior ESI 0.95, surgery and no prior ESI 0.78 (P = 0.15); no surgery and prior ESI 0.28, no surgery and no prior ESI 0.29 (P = 0.85). When adjusted for confounding factors, the reduction in SSM-symptom score was greater for surgery than for nonoperative treatment by 0.41 points (P < 0.001); the effect of having had an ESI prior to study entry was −0.08 (P = 0.40). Conclusion. The analysis of outcomes in the LSOS cohort provided no evidence that ESIs have a negative effect on the short-term outcome of surgery or nonoperative treatment in patients with lumbar spinal stenosis. Level of Evidence: 3